The first postoperative-stimulated serum thyroglobulin is a prognostic factor for thyroid microcarcinomas - Amui, Isabela de Oliveira; Tagliarini, José Vicente; Castilho, Emanuel C.; Marques, Mariângela de Alencar; Kiy, Yoshio; Corrente, José Eduardo; Mazeto, Gláucia M.F.S. (Elsevier, 2017)
Introduction: Endogenous thyroid-stimulating hormone-stimulated thyroglobulin collected after total thyroidectomy is a useful predictor of better prognosis in patients with differentiated thyroid carcinomas in general, but studies with microcarcinomas are scarce. Objective: To assess whether the first postoperative stimulated thyroglobulin measurement is a prognostic factor in patients with microcarcinoma. Methods: The medical data of 150 differentiated thyroid carcinoma patients were studied retrospectively, and 54 (36%) cases with microcarcinoma were selected. The first postoperative stimulated thyroglobulin (1st stimulated thyroglobulin), measured after thyroidectomy, initial presentation data, and microcarcinomas treatment were assessed regarding outcome. Worse prognosis was defined as neoplasm persistence/recurrence. Results: Persistence/recurrence occurred in 27.6% of the cases. These patients were identified according to the following parameters: receiving more than one 131iodine dose (100% vs. 0%; p <0.0001); accumulated 131iodine dose (232.14±99.09 vs. 144±33.61mCi; p <0.0001); presented active disease in the last assessment (53.3% vs. 0%; p <0.0001); follow-up time (103.07±61.27 vs. 66.85±70.14 months; p =0.019); and 1st stimulated thyroglobulin (19.01±44.18 vs. 2.19±2.54ng/dL; p <0.0001). After multivariate logistic regression, only the 1stSTg [odds ratio=1.242; 95% confidence interval: 1.022-1.509; p =0.029] and follow-up time (odds ratio=1.027; 95% confidence interval: 1.007-1.048; p =0.007) were independent predictors of risk of persistence/recurrence. The cutoff point of 1.6ng/dL for the 1st stimulated thyroglobulin was significantly associated with disease persistence/recurrence [area under the curve=0.713 (p =0.019)]. Conclusion: The first stimulated thyroglobulin predicted disease persistence/recurrence in patients with microcarcinoma.
Keywords: Biological markers; Clinical evolution; Prognosis; Thyroglobulin; Thyroid neoplasms